First‐ever acute ischemic strokes in HIV‐infected persons: A case–control study from stroke units - Romain Stammler; Jessica Guillaume; Mikael Mazighi; Christian Denier; Igor Raynouard; Bertrand Lapergue; Thomas De Broucker; Elena Meseguer; Hassan Hosseini; Anne Leger; Didier Smadja; Catherine Lamy; et al. (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective The stroke risk for persons living with human immunodeficiency virus (PLHIVs) doubled compared to uninfected individuals. Stroke‐unit (SU)—access, acute reperfusion therapy—use and outcome data on PLHIVs admitted for acute ischemic stroke (AIS) are scarce. Methods AIS patients admitted (01 January 2017 to 31 January 2021) to 10 representative Paris‐area SUs were screened retrospectively from the National Hospitalization Database. PLHIVs were compared to age‐, initial NIHSS‐ and sex‐matched HIV‐uninfected controls (HUCs). Outcome was the 90‐day modified Rankin Scale score. Results Among 126 PLHIVs with confirmed first‐ever AIS, ~80% were admitted outside the thrombolysis‐administration window. Despite antiretrovirals, uncontrolled plasma HIV loads exceeded 50 copies/mL (26% of all PLHIVs; 38% of those ≤55 years). PLHIVs' stroke causes by decreasing frequency were large artery atherosclerosis (LAA), undetermined, other cause, cerebral small‐vessel disease (CSVD) or cardioembolism. No stroke etiology was associated with HIV duration or detectable HIVemia. MRI revealed previously unknown AIS in one in three PLHIVs, twice the HUC rate (p = 0.006). Neither group had optimally controlled modifiable cardiovascular risk factors (CVRFs): 20%–30% without specific hypertension, diabetes, and/or dyslipidemia treatments. Their stroke outcomes were comparable. Multivariable analyses retained good prognosis associated solely with initial NIHSS or reperfusion therapy. Older age and hypertension were associated with CSVD/LAA for all PLHIVs. Standard neurovascular care and reperfusion therapy were well‐tolerated. Interpretation The high uncontrolled HIV‐infection rate and suboptimal CVRF treatment support heightened vigilance to counter suboptimal HIV suppression and antiretroviral adherence, and improve CVRF prevention, mainly for younger PLHIVs. Those preventive, routine measures could lower PLHIVs' AIS risk.